From “Anti-inflammatory Medicine” to Public Resource: Antibiotic Culture, Intergenerational Memory, and the Ethics of AMR Governance in China - Jingyi Yang (International Journal of Biology and Life Sciences, 2026)
The abuse of antibiotics in China cannot be considered solely a consequence of the scientific illiteracy of the population. On the contrary, one needs to look at this phenomenon in the context of historically developed “antibiotic culture” which can be seen through history. From penicillin as a symbol of modern medicine and national salvation to the role of barefoot doctors and primary health care in the distribution of antibiotics in rural China to the liberalization of health care following Reform and Opening-up, antibiotics have increasingly become for many people “effective anti-inflammatory medicines.” Due to the cultural memory, different generations perceive disease, infection, doctors, and pharmacies differently. However, in the wake of the growing antimicrobial resistance crisis that poses a threat to the public health globally, antibiotics have been re-conceptualized as resources requiring collective effort in its preservation. This creates ethical dilemmas both in terms of misuse reduction and providing access to reliable and affordable treatment for those who still need antibiotics. The essay will discuss possible solutions to these dilemmas.